1998
DOI: 10.1212/wnl.51.2.433
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in young adults with infratentorial infarcts

Abstract: Cerebellar damage impairs central aspects of attention and visuospatial skills. In contrast, intelligence and episodic memory remain unchanged. When the lesion involves large portions of the cerebellar hemispheres, changes concerning broad areas of intelligence may occur. The prognosis is favorable for neurologic dysfunction, but cognitive deficits may prevent return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(110 citation statements)
references
References 15 publications
7
90
1
12
Order By: Relevance
“…A subsequent study, however, did not replicate these results, but rather found an inverse correlation between the lesion volume and the cognitive impairments [27]. Our results showed that the mean lesion size of the patients with neglect was much larger than those without neglect supporting Malm et al's result [26]. Although the reason for this discrepancy is not entirely clear, our patients' lesions appeared to be larger than those of Kalashnikova et al's patients [27] and even larger than those of the cognitively normal group in their study.…”
Section: Lesion Sizecontrasting
confidence: 58%
See 1 more Smart Citation
“…A subsequent study, however, did not replicate these results, but rather found an inverse correlation between the lesion volume and the cognitive impairments [27]. Our results showed that the mean lesion size of the patients with neglect was much larger than those without neglect supporting Malm et al's result [26]. Although the reason for this discrepancy is not entirely clear, our patients' lesions appeared to be larger than those of Kalashnikova et al's patients [27] and even larger than those of the cognitively normal group in their study.…”
Section: Lesion Sizecontrasting
confidence: 58%
“…One study found a clear correlation between cognitive impairments and the CT-based estimates of infarct size [26]. A subsequent study, however, did not replicate these results, but rather found an inverse correlation between the lesion volume and the cognitive impairments [27].…”
Section: Lesion Sizementioning
confidence: 96%
“…11␤-HSD activity was detected in both human cerebellum and hippocampus, with higher activity in cerebellar homogenates, suggesting that this may also be the case in humans. Although the function of 11␤-HSD1, and indeed of glucocorticoids, in the cerebellum is unclear, this structure is known to be involved in cognition in humans (55,56). The hippocampus and frontal cortex are more clearly related to cognition and here glucocorticoids play well defined roles modulating learning and memory (57).…”
Section: Discussionmentioning
confidence: 99%
“…Prefrontal and parietal cortex regions form circuits with cerebellar regions, and both imaging studies (Stoodley and Schmahmann 2009;Marvel and Desmond 2010) and studies of patients with brain damage (Malm et al 1998) implicate the cerebellum in working-memory manipulation. Moreover, a frontostriatal -cerebellar circuit is thought to have a general control function in resource-demanding long-term and workingmemory tasks (Marklund et al 2007a).…”
Section: How Can Information In Working Memory Be Manipulated and Updmentioning
confidence: 99%